Research of functional status of handball player is in a training process - Volodymyr Bogush; Oleksandr Yatsunskiy; Olga Sokol; Irina Smirnova; Oksana Reznichenko; Olga Kuvaldina (Kharkiv State Academy of Physical Culture, 2016)
Purpose: to learn functional changes in the organism of sportsman in the conditions of training process for optimization of sporting preparation of handball player. Material & Methods: the handball player of different age groups and sporting qualification inspected: 13-15 years without a sporting digit, 16-18 years is the second digit, 19-23 years is the first digit and candidates in masters of sport, in all 45 persons. Sensomotorni reactions, exactness of dosage of muscular efforts, limit of the line of sight, frequency of cardiac reductions, maximal consumption of oxygen, general and special capacity, were studied. Results: showed that an increase in the level of training significantly improved response sensorimotor systems (visual, auditory, motor), increased limits the field of vision that promotes a special game quality - the ability to see the field increased general and special performance, the optimum duration of intensive work is the heart rate and oxygen consumption, when a specific task training is a definite change in physiological systems. Conclusions: objective assessment and analysis of changes in the studied parameters of the functional state of an athlete revealed their relationship, which can be used in the training process.